Kursus asas keibubapaan Muslim dalam memenuhi keperluan ibubapa masa kini : satu kajian kes - Nik Abdul Rahman , Nik Suryani; Rais, Haniza; Hussien, Suhailah (Yayasan Takmir, 2007)
This study aimed at evaluating the effectiveness of a Basic Islamic Parenting (BIP) course in providing information, awareness, and skills on various aspects of parenting. It also attempted to list major concerns and issues in parenting that can help improve future related courses. Data were obtained through a survey and an open standardized interview. In general, a sample of 31 participants who participated in this study was satisfied with the effectiveness and comprehensiveness of the content of the course. They also conceded that the program was successful in integrating Islamic and Western inputs in it. Issues pertaining to the need for general and specific parenting skills, information and supports were the main concerns raised during the interviews. The study concluded that the findings of this case study need to be properly incorporated in future BIP programmes to ensure the needs of both Muslim parents and children are adequately met.